Development of Rift Valley fever virus candidate vaccines and reagents produced in Nicotiana benthamiana - Mbewana, Sandiswa (Department of Molecular and Cell Biology, 2017)
Rift Valley fever (RVF) is a haemorrhagic fever agent caused by an infection with an enveloped negative-stranded RNA Rift Valley fever virus (RVFV). It belongs to the genus Phlebovirus in the family Bunyaviridae. The virus is spread by infected mosquitoes and affects ruminants and humans, causing high numbers of neonatal fatalities in animals and occasional fatalities in humans. It is endemic to parts of Africa and the Arabian Peninsula, but is described as an emerging virus due to the wide range of mosquitoes that could spread the disease into non-endemic areas, posing serious health and agricultural problems. The disease can be prevented by vaccination, but there is currently no Food and Drug Administration-approved RVFV vaccine that can be used outside endemic areas, while there are two live attenuated vaccines available for use in endemic areas. These vaccines have the potential for reversion, and are therefore not recommended for use in countries where RVFV is not endemic. This indicates the need for more RVFV vaccine research and development. This work focused on the development of a RVFV vaccine candidate that would allow for differentiation between infected and vaccinated animals as well as humans.